Telaah Robotika Ibnu Ismail Al-Jazari - Muhammad Faqih Nidzom; Muhammad Taqiyuddin; Hani'atul Mabruroh; Ahmad Luqman Sudarsono; Muhammad Safari (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The development of technology in the 4.0 era is very significant, and robotics is part of technological advances that can be felt today. He has helped a lot in human development and civilization in all aspects. When it comes to robotics, the name Da Vinci is undoubtedly the front guard. Even though there are also Muslim scientists who we are aware of their contribution to in robotics, namely Abū al-'Iz Ibn Ismā'īl ibn al-Razāz al-Jazarī or better known as Al-Jazari. This article discusses the concept of robotics according to al-Jazari and its contribution to technological development using qualitative methods. Here it is found that the study of technology developed by Muslim scientists, especially al-Jazari, makes use of the natural forces in the surrounding environment to facilitate their work. Pure technology and utilitarian technology which is a branch of the technology developed by al-Jazari, resulted in an ingenious invention, namely the third water treatment device. Al-Jazari combines the two branches of knowledge into a mechanical tool that has never been found before. Since the beginning he has emphasized the importance of experimentation and proper observation, as well as paying attention to the axiological or objective aspects of science and the findings.